Factores de riesgo asociados a fisuras labio palatinas en niños menores de 12 años atendidos en un hospital de tercer nivel del Minsa 2023 - Curico Huanci, Greisi Elena (2024)
The objective was to determine the risk factors associated with cleft lip and palate in children under 12 years of age attended in a third level hospital MINSA 2023, the method was quantitative and analytical design of cases and controls. The population and sample consisted of 77 cases and 154 controls matched by main characteristics such as age and sex, from different areas of the Peruvian Amazon. The technique used was an interview and the instrument was a questionnaire of risk factors associated with cleft lip and palate. The statistical program Epiinfo version 7.2 was used for data processing and analysis. The results show that 70% of the children were aged 0 - 6 years, with a mean of 4.56 years and SD 3.24; 55% were male, 64.07% were from rural areas. Of the mothers, 81.02% were under 35 years of age, 45.84% had complete prenatal control, 82% consumed folic acid, 8% had a family history, 11% had comorbidity, 76% were housewives, only 4% consumed tobacco or other substances and 6% consumed alcohol during the first months of pregnancy.A statistically significant association was found between complete prenatal control, folic acid consumption (OR1 CI: 95%) (p0.05).